Whole genome sequencing of Ethiopian Brucella abortus isolates expands the known diversity of an early branching sub-Saharan African lineage - Edao, Bedaso Mammo; Ameni, Gobena; Berg, Stefan; Tekle, Muluken; Whatmore, Adrian M.; Wood, James L. N.; van Tonder, Andries J.; Ashford, Roland T. (Frontiers in Microbiology, 2023)
Brucellosis remains one of the most significant zoonotic diseases globally, responsible for both considerable human morbidity and economic losses due to its impacts on livestock productivity. Despite this, there remain significant evidence gaps in many low- and middle-income countries, including those of sub-Saharan Africa. Here we report the first molecular characterisation of Brucella sp. from Ethiopia. Fifteen Brucella sp. isolates from an outbreak in cattle from a herd in central Ethiopia were identified as Brucella abortus, using bacterial culture and molecular methods. Sequencing of the Ethiopian B. abortus isolates allowed their phylogenetic comparison with 411 B. abortus strains of diverse geographical origins, using whole genome single nucleotide polymorphisms (wgSNP). The Ethiopian isolates belonged to an early-branching lineage (Lineage A) previously only represented by data from two strains, both of sub-Saharan African origin (Kenya & Mozambique). A second B. abortus lineage (Lineage B), also comprised solely of strains originating from sub-Saharan Africa, was identified. The majority of strains belonged to one of two lineages of strains originating from a much broader geographical range. Further analyses based on multi-locus sequence typing (MLST) and multi-locus variable-number tandem repeat analysis (MLVA) expanded the number of B. abortus strains available for comparison with the Ethiopian isolates and were consistent with the findings from wgSNP analysis. MLST profiles of the Ethiopian isolates expanded the sequence type (ST) diversity of the early branching lineage of B. abortus, equivalent to wgSNP Lineage A. A more diverse cluster of STs, equivalent to wgSNP Lineage B, was comprised solely of strains originating from sub-Saharan Africa. Similarly, analysis of B. abortus MLVA profiles (n = 1891) confirmed that the Ethiopian isolates formed a unique cluster, similar to only two existing strains, and distinct from the majority of other strains of sub-Saharan African origin. These findings expand the known diversity of an under-represented lineage of B. abortus and suggest a potential evolutionary origin for the species in East Africa. In addition to providing information concerning Brucella species extant within Ethiopia this work serves as the basis for further studies on the global population structure and evolutionary history of a major zoonotic pathogen.